2018
DOI: 10.1007/s00262-018-2202-4
|View full text |Cite
|
Sign up to set email alerts
|

CD11c+ MHCIIlo GM-CSF-bone marrow-derived dendritic cells act as antigen donor cells and as antigen presenting cells in neoepitope-elicited tumor immunity against a mouse fibrosarcoma

Abstract: Dendritic cells play a critical role in initiating T-cell responses. In spite of this recognition, they have not been used widely as adjuvants, nor is the mechanism of their adjuvanticity fully understood. Here, using a mutated neoepitope of a mouse fibrosarcoma as the antigen, and tumor rejection as the end point, we show that dendritic cells but not macrophages possess superior adjuvanticity. Several types of dendritic cells, such as bone marrow-derived dendritic cells (GM-CSF cultured or FLT3-ligand induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The 279 peptides were randomly grouped into 56 pools of 4 to 5 peptides per group. Mice were immunized prophylactically with each group using bone marrow–derived DCs (BMDCs) as adjuvants ( 8 ). In order to prevent discrepancies in peptide uptake due to competition, BMDCs were separately pulsed with each individual neoepitope from the group.…”
Section: Resultsmentioning
confidence: 99%
“…The 279 peptides were randomly grouped into 56 pools of 4 to 5 peptides per group. Mice were immunized prophylactically with each group using bone marrow–derived DCs (BMDCs) as adjuvants ( 8 ). In order to prevent discrepancies in peptide uptake due to competition, BMDCs were separately pulsed with each individual neoepitope from the group.…”
Section: Resultsmentioning
confidence: 99%
“…The 8 MS-defined neoepitopes were used to immunize naive BALB/cJ mice twice, 1 week apart, with neoepitope-pulsed bone marrow–derived dendritic cells (BMDCs, 3 × 10 6 ) as adjuvants, as previously published (22). All mice were challenged with 95,000 Meth A tumor cells 1 week after the second immunization, and tumor growth was monitored in individual mice (Figure 2, A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Because of these benefits, cancer vaccines have recently received a significant amount of interest [ 68 ]. In mouse fibrosarcoma, dendritic cells generated from GM-CSF served as both antigen-presenting cells and antigen donors [ 69 ]. Studies also revealed that combining photodynamic therapy (to boost antigen-presenting ability) with a dendritic cell vaccine can generate an efficient immune response in squamous cell carcinoma patients [ 70 ].…”
Section: Strategies Used In Cancer Immunotherapymentioning
confidence: 99%